Virtual reality mini map presentation techniques: Lessons and experience learned - Mahalil I.; Yusof A.M.; Ibrahim N.; Mahidin E.M.M.; Rusli M.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
Chemical activation; Helmet mounted displays; Virtual reality; Destination points; End users; Head mounted displays; Map activation; Virtual worlds; User experience